The effect of environmental factors on oats resistance to loose smut - Т. P. Gradoboeva; G. A. Batalova (Зерновое хозяйство России, 2020)
Loose smut (Ustilago avenae (Pers.) Rostr.) is the most dangerous and harmful disease with a wide distribution area. The purpose of the current study was to screen spring oat genotypes for resistance to loose smut and the stability of this trait on an artificial infectious background, and to identify resistant forms. There has been established that the large varieties damage in the first 5–10 days after sowing infected seed was caused by negative temperatures on the soil surface (correlation coefficient (r) was 0.95 and 0.90, respectively), and by average daily air temperature (r = 0.94–0.76), the minimum temperature on the soil surface (r = 0.86 and 0.82) and soil temperature at a depth of 5 cm (r = 0.87 and 0.78). The effect of precipitation was noted in a later period of 30–60 days after sowing (r = 0.88–0.72). On an infectious background there have been estimated 296 chaffy and hulled oats varieties. Among them there have been identified the genotypes with very high (188h12, 256h12, I-4845, 213h13, 233h13 and 256h13) and practical (119h11, 178h13, 194h13, 245h14, I-4857 and I-4903) resistance to the pathogen of 0 to 5%. In conditions of the natural development of the disease, the samples from the USA and Germany prevailed among foreign varieties with a lack of damage signs. Among the domestic ones the best results were identified in the varieties from Kirov and Ulyanovsk regions, Krasnodar Territory. The varieties 188h12, 256h12, I-4845 did not respond to changes in the environment (bi = 0). The parameters of variability (V), stability (S2), and stress resistance (xmin – xmax) of these genotypes were 0. The varieties 119h11 showed high stability (S2 = 2.2) and stress resistance (xmin – xmax = –3.7) of the trait. The oats varieties, selected due to loose smut resistance and due to stability of this trait on an infectious background are of great importance in breeding varieties with resistance to this disease.